Classical Complement (CH 50 ) activity among children with some bacterial and parasitic infections in Sokoto, Nigeria - Kalgo, M.U.* , Muhammad, T.B. , Yeldu, M.H. , Garba, B.I. , Hamid, K.M. , Isiyaku, A. , Raji, H.Y. , Bello, M. , Bunza, N.M. Garba, M.R. (Sokoto Journal of Medical Laboratory Science)
Complement system is a biochemical cascade that helps, or “complements” the ability of antibodies to clear pathogens from the body of an infected individual. Deficiency of any of the complement proteins may lead to recurrent infection and sepsis. This study evaluated the activity of the complement protein (CH 50 ) among children with some bacterial and parasitic infections, attending Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto, Nigeria. A total of 71 children, comprising of 45 males and 26 females suffering from either parasitic or bacterial infection, were recruited from the Emergency Paediatric Unit (EPU) of UDUTH. Socio-demographic characteristics of the study subjects were obtained with the aid of structured interviewer- administered questionnaire, while the presence of parasitic and bacterial infection was confirmed using microscopy and culture techniques respectively. Blood samples were collected from the children and processed to obtain serum. The serum CH 50 activity was assayed using sandwich Enzyme-linked Immunosorbent Assay (ELISA). The result indicated no significant (p = 0.294) differences between the assayed CH 50 activity and different microbial infections. Similarly, age, gender, and residence of the participants appeared not to be a factor affecting classical complement activity of children with microbial infections. Further studies are hereby suggested to explore the various mechanisms of complement CH 50 activity in the defense against microbial infections.